Socioterminologia da indústria madeireira - LIMA, Alcides Fernandes de (Universidade Federal do Ceará, 2017)
The work entitled “Socioterminology of Wood Industry” aims essentially at developing a terminological dictionary (or specialized dictionary) on wood. The theoretical and methodological foundations and the terminographic tasks for the elaboration of the dictionary are based on the communicative theory of terminology (Cabré 2002) and especially on socioterminology (Gaudin, 1993a, 1993b). To build the dictionary, we used a corpus of over 4,000,000 words (over 11,000 pages) composed of written texts about timber activities and having different degrees of specialization (such as theses and monographs, articles , technical norms, journals and magazines) with the exception of lexicographic documents or norms published between 1976 and 2009. The result of this work is a dictionary presented in two versions, printed and electronic. The electronic version (on CD-ROM) contains 2081 lexical entries, including: i) 1089 words (685 entries and 404 variants) from wood activities covering the semantic fields: mining, raw materials, processing, machinery and equipment, facilities, products, industrial waste and market ii) 886 words composed of 247 names of timber species and 639 variants, and iii) 106 initials (abrieviations) accompanied by syntactic variants (without definition). To the electronic version we have added up to 133 illustrations. As for the printed version, the initials were organized separately, the names of timber species have been grouped in a glossary of terms (without défintions) at the end of the dictionary to make it easier for users when looking for information on the terms and names of timber species. We believe that with the increasing need for the state to monitor and control the activity of wood industry and the development of research in various disciplines on economic activity, or other areas still connected to wood industry (given that most environmental problems today are related to forest management), work in terminology, as the one presented here, seem undoubtedly of great importance not only for industry and government sectors, but also for other sciences involved in this field such as agronomy, ecology, biology, botany, zoology, wood engineering and economics. Therefore, we seek in this work to contribute to the documentation and standardization of the lexicon related to the specialized field of wood activity and to create a basis for a better communication between different fields and between public and private sectors.